ANALISIS ALIH KODE DAN CAMPUR KODE DALAM KONTEN YOUTUBE NAURA AYU “ SERING DI BULLY MEMBUAT CINTA LAURA MENERIMA DIRINYA SENDIRI I NAW YOU TELL ME ! Eps 12 “ - Dea Stepani; Lia Sari; Marlina Dwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The philosophy of education is the product of deep thought and meditation upon education. Philosophy is the way out and education follows it and the problems of education can be answered using philosophy. The goal of research is to describe dsara's school knowledge with educational philosophy. The author compiled the data into a journal article. ranging from 2018 to 2022. Homeschooled results from the Google schoolar electronic database. May result in the importance of the implanting of a elementary school philosophy of education that becomes a formal school education that makes a child a guiding child in his or her stages of life